PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUASAN PELANGGAN MAXIM DI KOTA BATAM - Strahel Idauli Kristin Marbun; Asron Saputra (SCIENTIA JOURNAL, 2022)
This study aims to determine the effect of service quality, product quality and promotion on Maxim's customers satisfaction in Batam simultaneously and partially. The sample# in this study were customers' of Maxim, in Batam, Sagulung sub-district and Batam City, totaling 400 respondents with non-probability sample method. The results of the study indicate that service quality, products quality and the promotion have a positive effect on customer satisfaction with the regression equation Y = 5.177 + 0.2481X1 + 0.301X2 + 0.280X3. The contribution of the influence of service quality, product quality and promotion to customer's satisfaction simultaneously is 68.8%, the calculated F value is greater than F tabe or (291.197 > 2.6049) with a significance of 0.000 < 0.05. There is a simultaneous positive and significant effect among service quality, products quality and promotion on customer's satisfaction.